2008
DOI: 10.1007/s00264-008-0596-x
|View full text |Cite
|
Sign up to set email alerts
|

Use of intramedullary fibular strut graft: a novel adjunct to plating in the treatment of osteoporotic humeral shaft nonunion

Abstract: Humeral shaft fractures respond well to conservative treatment and unite without much problem. Since it is uncommon, there is not much discussion regarding the management of nonunion in the literature, and hence this is a challenge to the treating orthopaedic surgeon. Osteoporosis of the fractured bone and stiffness of the surrounding joints compounds the situation further. The Ilizarov fixator, locking compression plate, and vascularised fibular graft are viable options in this scenario but are technically de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 10 publications
2
38
1
2
Order By: Relevance
“…Vascularized fibular graft increases the complexity and cost of osteosynthesis. 22 In our study, all patients treated with LCP and bone grafting achieved 100% union. Our results were similar to Ring et al and Kumar et al 23,24 We would like to highlight the use of LCP in younger patients as it has good outcome and patients can achieve higher activity levels with heavier demand on upper extremity function.…”
Section: 10supporting
confidence: 48%
See 1 more Smart Citation
“…Vascularized fibular graft increases the complexity and cost of osteosynthesis. 22 In our study, all patients treated with LCP and bone grafting achieved 100% union. Our results were similar to Ring et al and Kumar et al 23,24 We would like to highlight the use of LCP in younger patients as it has good outcome and patients can achieve higher activity levels with heavier demand on upper extremity function.…”
Section: 10supporting
confidence: 48%
“…Ten patients (56%) were treated by traditional bone setters, eight (44%) patients had some form of internal fixation, (nails=2, LCP=4, DCP=2). The mean duration of nonunion was 18.3 months (range [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. In patients treated by traditional bone setters seven had atrophic type, two had gap nonunion, one had pseudoarthrosis.…”
Section: Methodsmentioning
confidence: 99%
“…2), the high cost associated with the procedure, and a risk of infection. Although Vidyadhara et al [29] showed concern regarding slow revascularization of the dead graft by creeping substitution or graft resorption, we did not encounter such problems.…”
Section: Discussionmentioning
confidence: 74%
“…It is associated with a high union rate, low complication rate, and rapid return to function [1,3,[6][7][8][9]. For pseudoarthrosis specifically, plate osteosynthesis is the gold standard [10][11][12][13][14]. It is generally accepted that the best face of a long bone for plate placement is the tension face; theoretically, this is the posterior face of the humerus [10,15].…”
Section: Introductionmentioning
confidence: 99%